Detection of cell‐free circulating BRAFV600E by droplet digital polymerase chain reaction in patients with and without melanoma under dermatological surveillance. (1st February 2020) - Calbet‐Llopart, N.; Potrony, M.; Tell‐Martí, G.; Carrera, C.; Barreiro, A.; Aguilera, P.; Podlipnik, S.; Puig, S.; Malvehy, J.; Puig‐Butillé, J.A.
Summary: Background: The p.V600E mutation in the BRAF protein is the most frequent mutation in cutaneous melanoma and is a recurrent alteration found in common benign naevi. Analysis of the cell‐free BRAF c.1799T>A, p.V600E mutation (cf BRAF V 600E ) in plasma has emerged as a biomarker for monitoring prognosis and treatment response in patients with melanoma. Objectives: To quantify cf BRAF V 600E levels in plasma from patients with melanoma and from patients without melanoma undergoing regular follow‐up of their melanocytic lesions, in order to assess the clinical significance of the test. Methods: We quantified cf BRAF V 600E by droplet digital polymerase chain reaction in plasma from 146 patients without melanoma undergoing continuous dermatological screening, from 26 stage III and seven stage IV patients with BRAF ‐mutant melanoma, and from 32 patients with melanoma who were free of disease for 3 or more years. Results: Among disease‐free patients and individuals without melanoma, 52% presented a high naevus count (> 50) and 49% had clinically atypical naevi. cf BRAF V 600E was detected in 71% of patients with stage IV melanoma and 15% with stage III, and in 1·4% of individuals without melanoma. No cf BRAF V 600E mutation was detected in disease‐free patients with melanoma. Individuals without melanoma had lower cf BRAF V 600E levels than patients with melanoma. We established a variant allelic frequency of 0·26% or 5 copies mL −1 of cf BRAF V 600E as the optimal cutoff value for identifying patients with melanoma with > 99% specificity. Conclusions: This study suggests that naevus‐related factors do not influence the detection of cf BRAF V 600E in individuals without melanoma, and supports the clinical diagnostic value of plasma cf BRAF V 600E quantification in patients with melanoma. What's already known about this topic? The analysis of the BRAF c.1799T>A (p.V600E) mutation in cell‐free (cf)DNA has emerged as a potential biomarker for monitoring prognosis and treatment response in patients with metastatic BRAF V600E melanoma. The BRAF V600E alteration is a common genetic alteration found in benign proliferations such as melanocytic naevi. No information exists about the impact of the number of common acquired naevi or the presence of clinically atypical naevi in cf BRAF V600E detection in an individual. What does this study add? The cf BRAF V600E mutation is detected in plasma from a reduced number of individuals without melanoma undergoing continuous dermatological follow‐up. A high number of naevi or the presence of clinically atypical naevi are factors that do not influence cf BRAF V600E detection in an individual. Both total cf BRAF concentration and cf BRAF V600E frequency are effective biomarkers in patients with advanced melanoma but not in patients at early stages or with micrometastases. What is the translational message? Detection of cf BRAF V600E in an individual is not influenced by naevus‐related factors. cf BRAF V600E is a robust and reliable biomarker that can be used in dermatological surveillance programmes.